Challenges and Opportunities of Information and Communication Technology Integration in Indonesian School Learning: A Critical Literature Review - Sitti Nurwalyah; Nova Amelia; Sitti Patima; Ibrahim Arifin (CV. Yazri Aksara Nusantara, 2025)
The integration of Information and Communication Technology (ICT) in school learning represents a strategic agenda in contemporary educational transformation. This study aims to comprehensively examine the challenges and opportunities of ICT integration in Indonesian school learning through a critical literature review approach. Data were collected through a systematic search of relevant scholarly articles published in reputable national and international journals between 2016 and 2025. A total of 15 selected studies were analyzed using thematic analysis to identify dominant patterns and key findings. The results indicate that major challenges in ICT integration include disparities in digital infrastructure access, limitations in teachers’ pedagogical competence, and varying levels of acceptance of digital learning platforms. Conversely, ICT integration also offers significant opportunities to enhance instructional flexibility, student motivation, and access to diverse learning resources. This review highlights that successful ICT integration depends not only on technological availability but also on systemic readiness and sustained policy support. The findings of this study provide a conceptual foundation for policymakers and educators in developing inclusive and sustainable digital curriculum management in schools.